2008
DOI: 10.1007/s10517-008-0157-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of anomeric pairs of lipophilic glycosides of N-acetylmuramyl-L-alanyl-D-isoglutamine

Abstract: We studied the capacity of anomeric pairs of alpha- and beta-dodecyl, alpha- and beta-(1-pentylhexyl), and alpha- and beta-cyclododecyl glycosides of N-acetylmuramyl-L-alanyl-D-isoglutamine (muramyl dipeptide) to stimulate the nonspecific resistance of mice to intraperitoneal infection of Staphylococcus aureus and Escherichia coli cultures. Intraperitoneal pretreatment with the test substances in a wide dose range increased survival of infected animals. No differences were found between the biological effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Lipophilic 1- O -acyl and 1- S -acyl groups do change MDP adjuvant activity 100 . A recent synthetic approach of O -glycoside is described in Scheme 9 101105 . It was reported that as the aglycone carbon number increased (R= 6 d< 6 a< 6 b< 6 c), the ability of MDP derivatives to stimulate NK cytotoxic activity also increased.…”
Section: Synthetic Approach Of Mdp Analogsmentioning
confidence: 99%
“…Lipophilic 1- O -acyl and 1- S -acyl groups do change MDP adjuvant activity 100 . A recent synthetic approach of O -glycoside is described in Scheme 9 101105 . It was reported that as the aglycone carbon number increased (R= 6 d< 6 a< 6 b< 6 c), the ability of MDP derivatives to stimulate NK cytotoxic activity also increased.…”
Section: Synthetic Approach Of Mdp Analogsmentioning
confidence: 99%
“…Mutarotation of carbohydrate anomers is a fundamental phenomenon in chemistry and of particular importance in synthesis when stereochemically pure products are targeted. The different anomers frequently possess distinct biological activities, but similar physicochemical properties that can hamper the isolation of each stereoisomer. Although mutarotation has been studied for many decades, it still remains difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of glycopeptides on the resistance to bacterial infection was studied on outbred albino mice aging 20-25 days and weighing 12-14 g (Stolbovaya nursery) [4]. MDP glycosides in a fi nal volume of 0.5 ml were injected intraperitoneally to animals with sepsis induced by S. aureus strain Wood 46 (do ses 0.15, 1.5, and 15 mg/kg) or Escherichia coli strain 264 (doses 3.75, 75 μg/kg, and 1.5 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…We previously attempted to attach a cyclic structure to the glycoside site of MDP. Biological activity of glycopeptide (β-cyclohexyl glycoside of MDP and β-adamantyl glycoside of MDP) increased [5,6,7], remained unchanged, or even decreased under these conditions (α-and β-cyclododecyl glycosides of MDP) [4].Here we evaluated the capacity of new cycloalkyl glycosides of MDP to increase the resistance of mice to infections with gram-positive and gram-negative bacteria and to stimulate the production of cytokines by human mononuclear cells. …”
mentioning
confidence: 99%